2011
DOI: 10.1159/000327203
|View full text |Cite
|
Sign up to set email alerts
|

UK National COPD Resources and Outcomes Project 2008: Patients with Chronic Obstructive Pulmonary Disease Exacerbations Who Present with Radiological Pneumonia Have Worse Outcome Compared to Those with Non-Pneumonic Chronic Obstructive Pulmonary Disease Exacerbations

Abstract: Background: Limited comparative data exist on the outcomes of patients presenting with chronic obstructive pulmonary disease (COPD) exacerbations with or without radiological pneumonia. Objective: To examine the outcome differences amongst these patients. Methods: We analysed 2008 UK National COPD audit data to examine the characteristics, management and outcomes, inpatient- and 90-day mortality and length of stay of patients admitted with COPD exacerbations. Results: Of 9,338 admissions, 16% (1,505) had chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
70
2
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 29 publications
5
70
2
3
Order By: Relevance
“…In this survey, 822,500 hospital-admitted patients with COPD exacerbations had on average a hospital stay of 4.3 days. In the study of Myint et al [8] , the LOS was markedly increased to 7-14 days in AECOPD patients with concomitant radiological findings of pneumonia. Although patients with concomitant infiltrates were more likely to suffer from comorbidities and a higher level of disability, radiological detection of pneumonia was still an independent risk factor for a longer hospital stay.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…In this survey, 822,500 hospital-admitted patients with COPD exacerbations had on average a hospital stay of 4.3 days. In the study of Myint et al [8] , the LOS was markedly increased to 7-14 days in AECOPD patients with concomitant radiological findings of pneumonia. Although patients with concomitant infiltrates were more likely to suffer from comorbidities and a higher level of disability, radiological detection of pneumonia was still an independent risk factor for a longer hospital stay.…”
mentioning
confidence: 88%
“…The strength of this study is its statistical power due to the high number of cases. Taking into account that in a recent review of inhospital management of AECOPD [12] up to 13% of COPD patients did not receive any X-ray upon admission, the study by Myint et al [8] in this journal might call for stricter management programs in the future.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Clearly, those identified by the necessity for hospital admission are those most likely to cause deterioration in HS, demonstrated by high rates of 1-year mortality after hospital admission for exacerbations [9,10]. Recently, a large survey of COPD admissions in the UK revealed that severity of exacerbations based upon unexpected radiological infiltrates may affect prognosis also in terms other than mortality [11,12.] In ambulatory patients for whom a course of corticosteroids and/or antibiotics is sufficient treatment for the exacerbations [5,8,13], the evidence also supports such a deleterious role, albeit with a less hazardous outcome.…”
Section: Introductionmentioning
confidence: 99%